The Impact of Institutional and Ecological Sustainability Systems on Resident Satisfaction Using Protected Area Management as an Example - Vujić, Amit; Trišić, Igor; Štetić, Snežana; Skenderović, Ibro; Nechita, Florin; Ujkanović, Enis; Ćatović, Azra; Ljajić, Samir (MDPI AG, 2025)
The Special Nature Reserve “Carska Bara” (CB) contains significant water resources and wetlands whose flora and fauna should be preserved. This protected area attracts a wide range of tourists, primarily those who love the world of nature. The aim of this research was to determine whether sustainable tourism affects the satisfaction of residents, which is the main hypothesis (H1). Also, the specific aim of this research is to define the state of tourism that can be influenced by the ecological and institutional dimensions, which is the auxiliary hypothesis (H2). This research used a quantitative methodology. A total of 910 residents living in the surrounding communities were surveyed for the study. The analysis of the research results concludes that sustainable tourism has a significant impact on the satisfaction of residents, which fully confirms hypothesis H1. The research results also indicate the importance of the ecological and institutional dimensions of sustainability on the state of tourism, which fully confirms hypothesis H2. The research results obtained may be significant for the management process of this protected area and for improving the conditions for sustainable forms of tourism.
Keywords: sustainability indicators; sustainable tourism; ecological sustainability; institutional sustainability; management systems